2016
DOI: 10.1590/s1679-87592016101806402
|View full text |Cite
|
Sign up to set email alerts
|

Macromedusae of Southern Brazil: temporal variation, population structure and biochemical composition

Abstract: The objectives of this study were to record the macromedusae species on the north coast of Santa Catarina, and to estimate their population dynamics and variations in their biochemical composition, based on the specimens obtained in the by-catch of artisanal shrimp fishing between January 2012 and October 2014. Cohort analysis was performed to evaluate the population dynamic of the most frequent species. Biochemical analyses of the umbrellas were conducted on their water, carbohydrate, protein, lipid, ash and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…Comparing the P, L, K content per WM in this study (Figure 2) with the gelatinous zooplankton composition analyses by several authors (Arai et al, 1989;Clarke et al, 1992;Malej et al, 1993;Lucas, 1994Lucas, , 2009Bailey et al, 1995;Dubischar et al, 2006;De Barba et al, 2016), we can observe that the content of these components is higher in P. physalis and V. velella with certain minor exceptions. Hence, for a similar WM, these two could be a better source of some of these components due to their low water content.…”
Section: Compositionsupporting
confidence: 74%
See 3 more Smart Citations
“…Comparing the P, L, K content per WM in this study (Figure 2) with the gelatinous zooplankton composition analyses by several authors (Arai et al, 1989;Clarke et al, 1992;Malej et al, 1993;Lucas, 1994Lucas, , 2009Bailey et al, 1995;Dubischar et al, 2006;De Barba et al, 2016), we can observe that the content of these components is higher in P. physalis and V. velella with certain minor exceptions. Hence, for a similar WM, these two could be a better source of some of these components due to their low water content.…”
Section: Compositionsupporting
confidence: 74%
“…When comparing the biochemical content per DM (Table 5) we observed that the range in the literature for protein was generally below the mean content determined in P. physalis and V. velella (Arai et al, 1989;Clarke et al, 1992;Malej et al, 1993;Lucas, 1994Lucas, , 2009Bailey et al, 1995;Dubischar et al, 2006;De Barba et al, 2016). Table 5 also depicts several exceptions, for example, the two cubozoans, Chiropsalmus quadrumanus and Tamoya haplonema (De Barba et al, 2016); as well as a few arctic species (Percy and Fife, 1981); Aglantha digitale (Ikeda, 1972); certain edible species (Khong et al, 2016); and the gonad tissue of A. aurita and Cyanea capillata (Lucas, 1994;Doyle et al, 2007). The higher presence of protein in the neustonic hydrozoans may be due to the protein-based blue pigment, protein-based venoms, chitin-protein complexes associated with the pneumatophore, or the protein in extracellular fluids (Lane et al, 1965;Gainey, 1972;Zagalsky and Herring, 1977;Tamkun and Hessinger, 1981;Roberts, 1992).…”
Section: Compositionmentioning
confidence: 76%
See 2 more Smart Citations
“…Distribución geográfica. Uruguay (Leoni et al, 2016); Brasil (Barba et al, 2016); noreste del Golfo de México (Segura-Puertas et al, 2009); suroeste del Golfo de México: Sistema Arrecifal Veracruzano (Ocaña-Luna et al, 2015).…”
Section: Descripciones Sistemáticasunclassified